Highly Efficient Purely Organic Phosphorescence Light‐Emitting Diodes Employing a Donor–Acceptor Skeleton with a Phenoxaselenine Donor. Issue 12 (20th February 2023) - Chen, Zijian; Li, Mengke; Gu, Qing; Peng, Xiaomei; Qiu, Weidong; Xie, Wentao; Liu, Denghui; Jiao, Yihang; Liu, Kunkun; Zhou, Jiadong; Su, Shi‐Jian
Abstract: Purely organic room‐temperature phosphorescence (RTP) materials generally exhibit low phosphorescence quantum yield ( ϕ P ) and long phosphorescence lifetime ( τ P ) due to the theoretically spin‐forbidden triplet state. Herein, by introducing a donor–acceptor (D–A) skeleton with a phenoxaselenine donor, three nonaromatic amine donor containing compounds with high ϕ P and short τ P in amorphous films are developed. Besides the enhanced spin–orbit coupling (SOC) by the heavy‐atom effect of selenium, the D–A skeleton which facilitates orbital angular momentum change can further boost SOC, and severe nonradiative energy dissipation is also suppressed by the rigid molecular structure. Consequently, a record‐high external quantum efficiency of 19.5% are achieved for the RTP organic light‐emitting diode (OLED) based on 2‐(phenoxaselenin‐3‐yl)‐4, 6‐diphenyl‐1, 3, 5‐triazine (PXSeDRZ). Moreover, voltage‐dependent color‐tunable emission and single‐molecule white emission are also realized. These results shed light on the broad prospects of purely organic phosphorescence materials as highly efficient OLED emitters especially for potential charming lighting applications. Abstract : A record‐high external quantum efficiency approaching 20%, voltage‐dependent color‐tunable emissions and single‐molecule white emissions are realized for purely organic electro‐phosphorescence device employing a room‐temperature phosphorescence emitter with a planar donor–acceptor skeleton and a phenoxaselenine donor.